PENGENTASAN KEMISKINAN MELALUI PENGEMBANGAN LEMBAGA DAKWAH - sukri sukri (Ath Thariq Jurnal Dakwah dan Komunikasi, 2019)
Proverty is a real reality that exists in every society, even this is a global prblem that afflicts all countries in the world, especially in Indonesia. In Indonesia alone poverty is a fairly complex problem and has a close relationship with various elements or elements. In a country and of course this requires a serious response by all parties, because it is not i Indonesia that based on Pancasila and UUD 45 is the realization of a just state prosperous just and evenly, so thus poverty is certainly the responsibility of all elements. Poverty reduction can bedone through three factors, namely individual obligations, obligations of others, and government obligations in carrying out obligations for policy polcies. Dakwah institutions demand responsbility to complete, or if empowering the community there must be an adequate result.